Insight into the Evolving Role of PCSK9 - Mateusz Maligłówka; Michał Kosowski; Marcin Hachuła; Marcin Cyrnek; Łukasz Bułdak; Marcin Basiak; Aleksandra Bołdys; Grzegorz Machnik; Rafał Jakub Bułdak; Bogusław Okopień (Metabolites, 2022)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) is the last discovered member of the family of proprotein convertases (PCs), mainly synthetized in hepatic cells. This serine protease plays a pivotal role in the reduction of the number of low-density lipoprotein receptors (LDLRs) on the surface of hepatocytes, which leads to an increase in the level of cholesterol in the blood. This mechanism and the fact that gain of function (GOF) mutations in PCSK9 are responsible for causing familial hypercholesterolemia whereas loss-of-function (LOF) mutations are associated with hypocholesterolemia, prompted the invention of drugs that block PCSK9 action. The high efficiency of PCSK9 inhibitors (e.g., alirocumab, evolocumab) in decreasing cardiovascular risk, pleiotropic effects of other lipid-lowering drugs (e.g., statins) and the multifunctional character of other proprotein convertases, were the cause for proceeding studies on functions of PCSK9 beyond cholesterol metabolism. In this article, we summarize the current knowledge on the roles that PCSK9 plays in different tissues and perspectives for its clinical use.